Epigallocatechin-3-gallate inhibits the collagen accumulation of oral submucous fibrosis induced by arecoline - Gao, Ge; Lin, Caipeng; Li, Ruibo; Xie, Xi; Luo, Hai-Bin (Frontiers in Pharmacology, 2025)
ObjectiveOral submucous fibrosis (OSF) is a chronic oral mucosal disease, which exerts a profound impact on patients’ daily life and currently lacks efficacious therapeutic interventions. Epigallocatechin-3-gallate (EGCG), the abundant polyphenol found in green tea, exhibits remarkable anti-fibrotic effects on the skin. However, the research on OSF regarding EGCG is relatively limited.PurposeWe aimed to investigate the potential therapeutic effect of EGCG against OSF using an arecoline (ARE) -induced rat model and primary rat oral fibroblasts.MethodsPrimary rat oral mucosal fibroblasts (ROMF) were isolated and identified. Optimal ARE concentrations were established using the Cell Counting Kit-8. The impact of ARE on extracellular matrix (ECM)-related protein expression was assessed through RT-qPCR and Western blot techniques. Similarly, the effects of EGCG on ARE-induced ECM changes in ROMF were evaluated. The study also established an OSF model in Sprague-Dawley rats, induced by ARE, with pathological changes characterized using HE and Masson’s staining, further assessing the impact of ARE on ECM-related protein expression in rat oral tissues through RT-qPCR and Western blot methods.ResultsEGCG effectively suppressed the ARE-induced ECM components while concurrently improving the OSF pathological process in vitro and in vivo.ConclusionThe results indicate that the natural product EGCG effectively suppressed the increased ECM components induced by ARE and concurrently improved the OSF pathological process, indicating that EGCG could be potentially a novel anti-fibrotic candidate drug for the treatment of OSF.